Irisin protects against neuronal injury induced by oxygen-glucose deprivation in part depends on the inhibition of ROS-NLRP3 inflammatory signaling pathway. (November 2017) - Peng, Juan; Deng, Xian; Huang, Wei; Yu, Ji-hua; Wang, Jian-xiong; Wang, Jie-ping; Yang, Shi-bin; Liu, Xi; Wang, Li; Zhang, Yun; Zhou, Xiang-Yu; Yang, Hui; et al.
Highlights: OGD significantly inhibited endogenous FNDC and irisin expression and release from PC12 cells in a time-dependent manner. Exogenous irisin mitigated OGD-induced neuronal injury in a dose-dependent manner. Exogenous irisin mediated the anti-oxidative stress and anti-inflammatory effects in part via ROS-NLRP3 inflammasome signaling. Abstract: Recent studies found that irisin, a newly discovered skeletal muscle-derived myokine during exercise, is also synthesized in various tissues of different species and protects against neuronal injury in cerebral ischemia. The NOD-like receptor pyrin 3 (NLRP3) inflammasome play an important role in detecting cellular damage and mediating inflammatory responses to aseptic tissue injury during ischemic stroke. However, it is unclear whether irisin is involved in the regulation of NLRP3 inflammasome activation during ischemic stroke. In the present study, PC12 neuronal cells were exposed to oxygen-glucose deprivation (OGD), exogenous irisin (12.5, 25, 50 nmol/L) or NLRP3 inhibitor glyburide (50, 100, 200 μmol/L) were used as an intervention reagent, NLRP3 was over-expressed or suppressed by transfection with a NLRP3 expressing vector or NLRP3-specifc siRNA, respectively. Our data showed that both irisin and its precursor protein fibronectin type III domain containing 5 (FNDC5) expression were significantly down-regulated ( p <  0.05); but oxidative stress and ROS-NLRP3 inflammasome signaling were activated by OGD ( p <  0.05); treatment with irisin or inhibition of NLRP3 reversed OGD-induced oxidative stress and inflammation ( p <  0.05). However, these irisin-mediated effects were blunted by over-expression NLRP3 ( p <  0.05). Taken together, our results firstly revealed that irisin mitigated OGD-induced neuronal injury in part via inhibiting ROS-NLRP3 inflammatory signaling pathway, suggesting a likely mechanism for irisin-induced therapeutic effect in ischemic stroke.